Teachers’ Challenges in Integrating 4Cs in General English Reading Instruction: Evidence from an Intensive English Program - Farouk Imam Arrasyid; Sri Wuli Fitriati; Puji Astuti; Zulfa Sakhiyya (Journal of General Education and Humanities, 2026)
The integration of 21st-century skills (4Cs) in EFL reading instruction has become a central expectation in higher education; however, its implementation in General English contexts remains uneven, particularly in Intensive English Programs (IEPs). This study aimed to investigate the difficulties lecturers encounter in integrating critical thinking, communication, collaboration, and creativity into reading instruction at UIN Siber Syekh Nurjati Cirebon. Using a qualitative case study design, data were gathered through classroom observations, semi-structured interviews with three lecturers, and document analysis of instructional materials. The data were analyzed thematically following Braun and Clarke’s framework. The findings revealed six interconnected challenges: procedural reading tasks, low cognitive demand, limited instructional time, superficial collaboration practices, insufficient cognitively directive instructional language, and assessment practices that prioritized accuracy over reasoning. These challenges indicate that the integration of the 4Cs is constrained not only by lecturers’ pedagogical decisions but also by task design, classroom implementation, and institutional program demands. The study concludes that effective integration of 4Cs in reading instruction requires greater attention to micro-level instructional design rather than relying solely on general pedagogical awareness. It is recommended that lecturers incorporate cognitively directive tasks, structured collaborative activities, and assessment practices emphasizing reasoning and interpretation. These findings contribute to a more nuanced understanding of how 4Cs can be operationalized in intensive EFL contexts.